The correlation between self-efficacy and motivation on elderly's daily independence - Setia W, Indra; Isnaini, Nur (Proceedings Series on Health & Medical Sciences, 2020)
Being old is a condition that happens in life and means experiencing a physical and psychological decline. Generally, it means experiencing weakness, limitation, and inability which affect one's life quality. Self-efficacy is closely related to independence, meaning that the higher self-efficacy the higher the ability to manage behaviour or independence will be. Independence in the elderly is affected by psychological energy, which depends on the level of motivation. The elderly having high motivation tends to be passionate. He/she is different from those having no motivation, who tend to be lazy and less understand the importance of health. This research to identify the correlation between self-efficacy and motivation on elderlies independence at Sudagaran Elderly Social Service House in Banyumas District. This research is a quantitative research using analytical observational design with a cross-sectional approach. The research sample consisting of 71 elderly people at Sudagaran Elderly Social Service House in Banyumas District were taken through purposive sampling. The research instrument was a questionnaire sheet. It was analysed using Chi-Square test. Most of the respondents are female (55.3%), have medium self-efficacy level (78.9%), have medium motivation level (67.7%), and are categorized independent (57.7%). The result of Chi-Square test for the self-efficacy obtains p-value of 0.002=0.05 and for the motivation obtains p-value of 0.022=0.05 on the elderly's daily independence. There is a correlation between self-efficacy and motivation on elderly's daily independence at Sudagaran Elderly Social Service House in Banyumas District.